ANALISIS STRATEGI PROMOSI AKUN INSTAGRAM TALAMCUTABANG DALAM MEMBANGUN BRAND AWARENESS - Hariati, Hariati; Yamin Asgha, Ashabul (Universitas Nahdlatul Ulama Kalimantan Timur, 2025)
This study aims to analyze the promotional strategy on the Talamcutabang Instagram account in building brand awareness. The theory used was the advertising exposure theory. The research method employed was a descriptive qualitative approach, with informants selected using purposive sampling. Data collection techniques included semi-structured interviews, observation, and documentation. The findings indicated that Talamcutabang has successfully established a strong presence in the top of minds of its consumers, with the brand consistently being the first to come to mind when people think about it. This is because consumers of Talamcutabang can remember and choose Talamcutabang as their first choice when compared to other brands. Consumers are also able to explain certain characteristics of Talamcutabang without being given a stimulus first. Additionally, consumers can mention the various products sold by Talamcutbang.